Convergence of Regional Social Order’s Indicators - Kusideł, Ewa (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The subject of convergence became popular in Poland upon its accession to the EU in 2004. On one hand, according to some politicians and economists, convergence is an expected outcome of integration, while, on the other hand, numerous research studies cast doubt on the effectiveness of the cohesion policy. The doubts are mainly based on two facts: the inability of supported regions to grow on their own after external assistance ceases to be provided and the presence of evidence confirming that interregional cohesion, being a standard until the late 1970s, does not occur anymore. Those facts pertain to economic convergence, verified on the basis of economic activity measures – it is most frequently the GDP per capita. However, the cohesion policy, carried out within the framework of the EU regional policy, has broader aspects: economic, social, and territorial (spatial) ones. While the economic aspect is a very thoroughly researched area of convergence studies, the social aspects are less often covered by specialist literature. It is that issue that is raised in this paper in which, instead of separate measures of social convergence, the synthetic measures of social cohesion of Polish provinces are presented.